Long-term oncological outcomes of laparoscopic gastrectomy for grossly early gastric cancer-mimicking advanced gastric cancer: Propensity score matching analysis. Issue 49 (4th December 2020) - Oh, Sung Eun; An, Ji Yeong; Choi, Min-Gew; Sohn, Tae Sung; Bae, Jae Moon; Lee, Jun Ho
Abstract : Abstract: Laparoscopic gastrectomy became an option in the treatment of early gastric cancer (EGC) in clinical practice. However, whether laparoscopic surgery for grossly EGC-mimicking advanced gastric cancer (AGC) patients is oncologically safe long-term is still controversial. We retrospectively analyzed 472 patients with AGC who were diagnosed as clinical EGC. Patients received laparoscopic or open gastrectomy with standard lymph node (LN) dissection from January 2007 to February 2015. We used a 1:3 propensity score matching method for the analysis. The matching factors were age, sex, body mass index, American Society of Anesthesiologists score and pathologic stage. After the matching process, we evaluated the 5-year overall survival and the cumulative incidence curve of recurrence. All of the analyzed patients were pathologically diagnosed with AGC after surgery (grossly EGC-mimicking AGC). The median (range) duration of follow-up was 58.0 (0–132) months. After propensity score matching, 31.5% of patients in the laparoscopy group had D1+ LN dissection and 99.2% of patients in the open group had D2 LN dissection. The 5-year overall survival rate between the laparoscopy (n = 92) and open groups (n = 244) were not significantly different (95.3% versus 91.4%, P  = .224). There was no significant difference between the cumulative recurrence incidence curves of the matched groups ( P  = .319). Laparoscopic surgery for grossly EGC-mimicking AGC might be safe in terms of long-term survival outcome. After confirming grossly EGC-mimicking AGC in the final pathology report, no additional surgery might be required.